1993
DOI: 10.1038/jcbfm.1993.6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bolus and Infusion Methods for Receptor Quantitation: Application to [18F]Cyclofoxy and Positron Emission Tomography

Abstract: Summary:Positron emission tomography studies with the opiate antagonist [18F]cyclofoxy ([18F]CF) were per formed in baboons. Bolus injection studies demonstrated initial uptake dependent on blood flow. The late uptake showed highest binding in caudate nuclei, amygdala, thal amus, and brainstem and the least accumulation in cere bellum. By 60 min postinjection, regional brain radioac tivity cleared at the same rate as metabolite-corrected plasma, i.e., transient equilibrium was achieved. Com partmental modeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
280
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(289 citation statements)
references
References 35 publications
9
280
0
Order By: Relevance
“…, 1988) and peak equilibrium methods (Farde et aI., 1986). We followed Carson et al (1992) by using the term transient equilibrium to designate the method that relies upon the measure of V a ( t ) when this value becomes constant (i.e. , when brain and plasma activity are decreasing at the same rate).…”
Section: Theory Three-compartment Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…, 1988) and peak equilibrium methods (Farde et aI., 1986). We followed Carson et al (1992) by using the term transient equilibrium to designate the method that relies upon the measure of V a ( t ) when this value becomes constant (i.e. , when brain and plasma activity are decreasing at the same rate).…”
Section: Theory Three-compartment Modelmentioning
confidence: 99%
“…Thus, a transient equilib rium state was not observed during the time frame of these experiments. Carson et al (1992) recently demonstrated that the transient equilibrium method overestimates the BP unless the brain washout (as estimated by k 2 ' or al) is much faster than A 3 ' In deed, at 300 min, the value of V a ( t ) was higher than that of VT . Thus, even if longer experimental times had allowed attainment of a transient equilibrium state in regions such as the striatum, this analysis would have overestimated VT • The peak equilibrium method is superior to the transient equilibrium method, at least theoretically,.…”
Section: Equilibrium Analysismentioning
confidence: 99%
“…These data suggest that relatively low degrees of occupancy are needed to induce clinically significant effects (Kling et al 1997). However, this study was conducted utilizing [ 18 F]cyclofoxy, which is a non-selective OR and kappa receptor marker (Carson et al 1993), and therefore the receptor availability measure calculated does not refer to one but two receptor sites. Since methadone has much higher affinity for mu than for kappa receptor sites (Kristensen et al 1995), the use of a non-selective radiotracer would underestimate changes in OR availability.…”
mentioning
confidence: 99%
“…Since the plasma drug concentration is not usually held con stant [generally the drug is administered as a bolus injection, although recently Carson et al (1993) have proposed an infusion protocol for e8p]cyclo foxy to maintain a constant plasma level], the tis sue/plasma drug ratio does not represent the true DV but also contains factors representing the loss of drug from plasma (Logan et aI., 1990 ;Carson et aI., 1993). Por this reason, when using a bolus in jection of tracer, the DV must be determined using compartmental modeling (finding values for individ ual kinetic parameters for a specified model) or graphically (not assuming a specified model) (Logan et aI., 1990).…”
mentioning
confidence: 99%